Transportation fuel portfolio design under evolving technology and regulation: A California case study - Chen, Yuche; Fan, Yueyue (Transportation research. Part D, Transport and environment, 2013)
•The study develops sustainable fuel portfolio under evolving technology and regulations.•Sustainability is measured by economic viability, emission, and adaptability.•Cellulosic ethanol technology readiness has a significant effect on fuel portfolio. In this paper, a multistage optimization model, which introduces a dynamic notion of sustainability, is established to identify a sustainable liquid fuel portfolio subject to evolving technology and environmental regulations. A case study based on California data is implemented to examine the impacts of cellulosic technology evolvement on liquid fuel industry, including the choice of fuel portfolio, the infrastructures needs, and the overall system cost and emission. It is found that cellulosic ethanol technology readiness has a significant effect on the choice of fuel portfolio and the expansion pattern of cellulosic ethanol industry, under the low carbon fuel standard, an environmental mandate in California.